Faktor-faktor yang mempengaruhi Akuntabilitas, Transparansi, dan partisipasi publik terhadap Kinerja organisasi layanan publik - Juwainah Ria; Rachmat Pramukty Warsoyo (Institut Nalanda, 2023)
This research aims to determine the influence of accountability, transparency and public participation on public service performance. The object of the research is the investment agency and integrated licensing agency of Ogan Ilir district. The research instrument is a questionnaire, where the service user community at the capital service investment agency in this research uses accountability, transparency and public participation as independent variables, while public service performance is the independent variable. The research results show that accountability, transparency and public participation have a positive influence on the performance of public service organizations.